2019
DOI: 10.1007/s11306-019-1553-y
|View full text |Cite
|
Sign up to set email alerts
|

Are we close to defining a metabolomic signature of human obesity? A systematic review of metabolomics studies

Abstract: Introduction Obesity is a disorder characterized by a disproportionate increase in body weight in relation to height, mainly due to the accumulation of fat, and is considered a pandemic of the present century by many international health institutions. It is associated with several non-communicable chronic diseases, namely, metabolic syndrome, type 2 diabetes mellitus (T2DM), cardiovascular diseases (CVD), and cancer. Metabolomics is a useful tool to evaluate changes in metabolites due to being overweight and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
178
3
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(207 citation statements)
references
References 203 publications
18
178
3
8
Order By: Relevance
“…73 Recently, studies have shown that the metabolomic signatures of blood from cattle 74 and pigs 75 can be used to accurately separate animals by their feed efficiency which is one of the most economically important traits in livestock production. Studies of the human metabolome and its relevance to human health has also clearly increased the last five years, 76,77 and is very likely to be one of the cornerstones in an implementation of personalised medicine. With the emergence of large human cohort projects, like the UK Biobank 78 , FinnGenn 79 and BioBank Japan 80 etc., the data samples are reaching a sample level that could provide ground-breaking research if full metabolomic profiles were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…73 Recently, studies have shown that the metabolomic signatures of blood from cattle 74 and pigs 75 can be used to accurately separate animals by their feed efficiency which is one of the most economically important traits in livestock production. Studies of the human metabolome and its relevance to human health has also clearly increased the last five years, 76,77 and is very likely to be one of the cornerstones in an implementation of personalised medicine. With the emergence of large human cohort projects, like the UK Biobank 78 , FinnGenn 79 and BioBank Japan 80 etc., the data samples are reaching a sample level that could provide ground-breaking research if full metabolomic profiles were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…RA patients present several comorbidities including obesity, metabolic syndrome, and sarcopenia, probably triggered by a disbalance of proinflammatory cytokines including TNF and IL-6 among other causes [73][74][75][76][77], that will modify the circulating metabolites [78]. Several studies have investigated circulating metabolic changes related to the metabolic syndrome and obesity [79,80]. Of interest, a lot of circulating metabolites that are different in RA patients compared to controls could be related to associated metabolic syndrome, since choline metabolism (especially TMAO and carnitine), aminoacids (alanine, glutamine, glutamate, arginine, aspartate, asparagine, histidine, methionine, cysteine, lysine, branched-chain amino acids (BCAA), phenylaniline, tyrosine, and tryptophan) and phospholipids (phosphatydilcholines) also change in those with metabolic syndrome [80].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…It carries information about gene expression as well as lifestyle-and environmental factors (Tzoulaki et al 2014;van Roekel et al 2019). Metabolomics has already been successfully applied in large-scale epidemiological studies, mainly in adult populations, to identify new biomarkers of cardio-metabolic disease status, development and progression, as well as the underlying pathophysiological mechanisms (Newgard 2017;Rangel-Huerta et al 2019;Ussher et al 2016).…”
Section: Introductionmentioning
confidence: 99%